PENGGUNAAN EM4 DALAM PAKAN BUATAN UNTUK MENINGKATKAN KEEFISIENAN PAKAN DAN PERTUMBUHAN IKAN NILA GIFT (Oreochromis sp.) - Farida Nur Rahmawati; Untung Susilo; Bambang Hariyadi (Universitas Tadulako, 2006)
The fish growth is influenced by the quality of food consumed. EM4 with difference doses (0, 5, 10, and 15 ml/kg diet) was carried out to investigate feed efficiency and the growth of nila gift. An experimental method based on completely randomized design in four replicates was used for 35 days. nila gifts with 12 – 18 g in body weight were used. Fishes were fed twice daily as much as 5% of their body weight and unfed one was taken an hour after feeding. The result showed that the differences of EM4 on diet did not affect feed efficiency and the growth of nila gift. However, EM4 suplementation on diet could increase its protein content.